Hydrogen-assisted decohesion associated with nanosized grain boundary κ-carbides in a high-Mn lightweight steel - Elkot, Mohamed Naguib; Sun, Binhan; Zhou, Xuyang; Ponge, Dirk; Raabe, Dierk (Acta materialia, 2022)
While age-hardened austenitic high-Mn and high-Al lightweight steels exhibit excellent strength-ductility combinations, their properties are strongly degraded when mechanically loaded under harsh environments, e.g. with the presence of hydrogen (H). The H embrittlement in this type of materials, especially pertaining to the effect of κ-carbide precipitation, has been scarcely studied. Here we focus on this subject, using a Fe-28.4Mn-8.3Al-1.3C (wt%) steel in different microstructure conditions, namely, solute solution treated and age-hardened. Contrary to the reports that grain boundary (GB) κ-carbides precipitate only during overaging, site-specific atom probe tomography and scanning transmission electron microscopy (STEM) reveal the existence of nanosized GB κ-carbides at early stages of aging. We correlate this observation with the deterioration of H embrittlement resistance in aged samples. While H pre-charged solution-treated samples fail by intergranular fracture at depths consistent with the H ingress depth (∼20 µm), age-hardened samples show intergranular fracture features at a much larger depth of above 500 µm, despite similar amount of H introduced into the material. This difference is explained in terms of the facile H-induced decohesion of GB κ-carbides/matrix interfaces where H can be continuously supplied through internal short-distance diffusion to the propagating crack tips. The H-associated decohesion mechanisms are supported by a comparison with the fracture behavior in samples loaded under the cryogenic temperature and can be explained based on dislocation pileups and elastic misfit at the GB κ-carbide/matrix interfaces. The roles of other plasticity-associated H embrittlement mechanisms are also discussed in this work based on careful investigations of the dislocation activities near the H-induced cracks. Possible alloying and microstructure design strategies for the enhancement of the H embrittlement resistance in this alloy family are also suggested. [Display omitted]